2009
DOI: 10.1073/pnas.0911351106
|View full text |Cite
|
Sign up to set email alerts
|

Markedly enhanced colon tumorigenesis in Apc Min mice lacking glutathione S-transferase Pi

Abstract: Glutathione transferases are a multigene family of proteins that catalyze the conjugation of toxic electrophiles and carcinogens to glutathione. Glutathione transferase Pi (GSTP) is commonly overexpressed in human tumors and there is emerging evidence that the enzyme has additional cellular functions in addition to its role in drug and carcinogen detoxification. To investigate the unique functions of this enzyme, we have crossed Gstp null mice with an initiated model of colon cancer, the Apc Min mouse. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 42 publications
4
45
0
1
Order By: Relevance
“…In current study statistically significant downregulation of GSTP1 was observed in brain tumor samples compared to control samples. Similar results have also been observed in breast cancer (Erlap et al, 2013), prostate cancer (Okino et al, 2007;Re et al, 2011) and colon cancer (Ritchie et al, 2009).Whereas conflicting results for GSTP1 expression pattern have been reported in some of other studies (Masood et al, 2011;Uchida et al, 2013). In present study, significant down-regulation of GSTP1 was observed in more advance grade of brain tumor samples when compared with early grade of brain tumor.…”
Section: Discussionsupporting
confidence: 88%
“…In current study statistically significant downregulation of GSTP1 was observed in brain tumor samples compared to control samples. Similar results have also been observed in breast cancer (Erlap et al, 2013), prostate cancer (Okino et al, 2007;Re et al, 2011) and colon cancer (Ritchie et al, 2009).Whereas conflicting results for GSTP1 expression pattern have been reported in some of other studies (Masood et al, 2011;Uchida et al, 2013). In present study, significant down-regulation of GSTP1 was observed in more advance grade of brain tumor samples when compared with early grade of brain tumor.…”
Section: Discussionsupporting
confidence: 88%
“…It is thus more likely that the product of GSTP1-converted thiazolides promotes the activation of the different MAP kinase pathways, rather than via inhibition of GSTP1. Along these lines is the surprising observation that GSTP1-deficient mice develop increased numbers of intestinal tumors in the APC min/ þ model (Ritchie et al, 2009), rather than having reduced tumor burden. This could indicate that even in vivo GSTP1 may enzymatically convert inactive endogenous or bacterial substances to tumoricidal products, which limits the growth and development of intestinal tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, few studies have suggested increased expression of GSTP1 as an indicator of premalignant and malignant changes (Aliya et al, 2003;Usarek et al, 2004) while others have suggested expression of GSTP1 as a sign of carcinogen exposure in the endothelial and oral tissues (Gajewska et al, 2007;Conklin et al, 2009). Few studies have also reported that loss of GSTP1 expression is suggestive of carcinogenesis (Okino et al, 2007;Ritchie et al, 2009). GSTP1 is genetically polymorphic, and two GSTP1 non-…”
Section: Introductionmentioning
confidence: 99%